2016
DOI: 10.1614/wt-d-15-00116.1
|View full text |Cite
|
Sign up to set email alerts
|

Giant Ragweed (Ambrosia trifida) Seed Production and Retention in Soybean and Field Margins

Abstract: As herbicide-resistant weed populations become increasingly problematic in crop production, alternative strategies of weed control are necessary. Giant ragweed, one of the most competitive agricultural weeds in row crops, has evolved resistance to multiple herbicide biochemical sites of action within the plant, necessitating the development of new and integrated methods of weed control. This study assessed the quantity and duration of seed retention of giant ragweed grown in soybean fields and adjacent field m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 26 publications
1
38
0
1
Order By: Relevance
“…High seed‐retention levels of Palmer amaranth were also reported in a survey in soybean crops across five states (Arkansas, Illinois, Missouri, Nebraska and Tennessee) where, on average 95–99% of seed production was retained at soybean maturity . High levels of seed retention (80%) have also been reported for giant ragweed ( Ambrosia trifida L.) at soybean harvest in Minnesota …”
Section: North American Soybean Cropping Systemsmentioning
confidence: 54%
See 1 more Smart Citation
“…High seed‐retention levels of Palmer amaranth were also reported in a survey in soybean crops across five states (Arkansas, Illinois, Missouri, Nebraska and Tennessee) where, on average 95–99% of seed production was retained at soybean maturity . High levels of seed retention (80%) have also been reported for giant ragweed ( Ambrosia trifida L.) at soybean harvest in Minnesota …”
Section: North American Soybean Cropping Systemsmentioning
confidence: 54%
“…30 High levels of seed retention (80%) have also been reported for giant ragweed (Ambrosia trifida L.) at soybean harvest in Minnesota. 36…”
Section: Seed Retention Of Dominant Weedsmentioning
confidence: 99%
“…Palmer amaranth is known to produce an average of 60,221 ± 21,991 seeds plant −1 in soybean production (Schwartz et al, 2016b), and other studies have shown Palmer amaranth to produce upward of 600,000 seeds plant −1 in the absence of interference (Keeley et al, 1987). Goplen et al (2016) showed that giant ragweed retained 80% of its seed at the time of soybean harvest, meaning that its addition to the soil seedbank could be substantially reduced through use of the iHSD. Additional weed species have been examined for seed retention at harvest in other cropping systems.…”
Section: Resultsmentioning
confidence: 99%
“…plant −1 in the absence of interference (Keeley et al, 1987). Goplen et al (2016) showed that giant ragweed retained 80% of its seed at the time of soybean harvest, meaning that its addition to the soil seedbank could be substantially reduced through use of the iHSD. Additional weed species have been examined for seed retention at harvest in other cropping systems.…”
Section: And Included Both Broadleaf and Grass Species Thatmentioning
confidence: 99%
“…Additionally, wheat allows the use of herbicides with alternative mechanisms of action that are more effective against herbicide-resistant populations of giant ragweed. In the event of weed escapes, wheat is harvested prior to giant ragweed seed production (Goplen et al 2016), preventing replenishment of the seedbank and allowing time for multiple mechanical and chemical weed control options following wheat harvest.…”
mentioning
confidence: 99%